2021
DOI: 10.21608/tsnj.2021.171341
|View full text |Cite
|
Sign up to set email alerts
|

Audio- Drama Nursing Intervention Utilizing Peer Education on Menstrual Hygiene and Sickness Management among Blind Adolescents

Abstract: Adolescence is a critical developmental stage. Blind adolescent girls are a group of disabled girls who needs a special care specifically during the menstruation.The study aimed to examine the effect of audio-drama nursing intervention utilizingpeer education on menstrual hygiene and sickness management among blind adolescents. Design: Quasi-experimental design (pre and posttest) was used to accomplish the present study. Setting: Al Noor institute for visually impaired students at Shebein El-kom City in Menouf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…This outcome is consistent with research conducted by Abd Elmegaly, Attia and Soliman (2019) which demonstrated that mothers of the students are represented the basic source of information regarding all aspects of productivity at one quarter of the students' sample. In a similar vein, Ahmed et al, (2021) shown that the majority of visually impaired girls consulted their moms for information on menstruation, whereas a smaller proportion turned to teachers and the media.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This outcome is consistent with research conducted by Abd Elmegaly, Attia and Soliman (2019) which demonstrated that mothers of the students are represented the basic source of information regarding all aspects of productivity at one quarter of the students' sample. In a similar vein, Ahmed et al, (2021) shown that the majority of visually impaired girls consulted their moms for information on menstruation, whereas a smaller proportion turned to teachers and the media.…”
Section: Discussionmentioning
confidence: 92%
“…The adolescent stage in a girl is recognized as a delicate and sensitive era, which signifies a shift from young girlhood to adulthood. (Amr, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in agreement with a study done by Abd Elmegaly, Attia and Soliman (2019) demonstrated that mothers of the students are represented the basic source of information regarding all aspects of productivity at one quarter of the students' sample. In the same way, Ahmed et al, (2021) shown that the majority of visually impaired young adult girls in schools consulted their moms for information on menstruation, whereas a smaller proportion turned to staff members and the mass media.…”
Section: Discussionmentioning
confidence: 95%
“…Nurses play an effective role in providing visually impaired adolescent girls with sufficient information regarding hygienic practices that was needed during menstruation to maintain themselves healthy (Amr, 2021). An essential component of health education for girls with visual disabilities is nursing instruction on feminine hygiene and symptom management (Amr, 2021).…”
Section: Introductionmentioning
confidence: 99%